Refugee labor market integration at scale: Evidence from Germany’s fast-track employment program - Jens Hainmueller; Moritz Marbach; Dominik Hangartner; Niklas Harder; Ehsan Vallizadeh (Proceedings of the National Academy of Sciences, 2026)
Governments face persistent challenges in integrating refugees into the local labor market, and many past interventions have shown limited impact. This study examines the Job-Turbo program, a large-scale initiative launched by the German government in 2023 to accelerate employment among refugees—primarily individuals from Ukraine and eight other major countries of origin. Using monthly administrative panel data from Germany’s network of public employment service offices and a difference-in-differences design, we find that the program significantly increased both caseworker–refugee contact and job placements over a 23-mo follow-up period. Among Ukrainian refugees, the exit-to-job rate nearly doubled. Effects were broad-based—spanning demographic subgroups, unemployment durations, skill levels, regions, and local labor-market conditions—and were concentrated in regular, unsubsidized employment. The program also raised both the rate and share of placements followed by sustained employment, consistent with improved placement quality. Other refugee groups saw meaningful gains as well, but increases in job placements were concentrated among males and in low-skilled jobs, with only limited effects for females. We detect no negative spillovers on contact rates or exit-to-job rates for unemployed German or other immigrant job seekers, finding no evidence of resource reallocation or displacement. The results offer insights for governments responding to displacement crises. They indicate that intensified job-search assistance—embedded within the early stage of integration and implemented at scale through public employment infrastructure—can meaningfully improve refugees’ labor-market outcomes, even amid significant arrivals.